Design of optical Z-adjuster - Foo, James Meng Ngee. (2008)
This report illustrates the relationship of MTF% of main scan and sub scan (Green, Red and Blue colour) with respect to temperature is also established. The scope of this dissertation involves the design and fabrication of an optical z-adjuster, which is used to simulate the raising of the chart to simulate 3-dimensional scanning.